Description of Community Knowledge, Attitudes, and Behavior towards Glaucoma in Taman Sari District, West Jakarta - Ritsia Anindita Wastitiamurti; Michael Indra Lesmana; Javier Immanuel (Jurnal MedScientiae, 2022)
Glaucoma is the second leading cause of preventable blindness globally. Today, more than 60 million people worldwide have glaucoma, with nearly half of these people developing the disease without knowing it. In 2010, there were 60.5 million individuals suffering from glaucoma. In 2020 it is estimated that the incidence of glaucoma globally will reach 76 million and 111.8 million in 2040. This can be prevented by early detection, but can only be done through screening. Therefore, there is a need for public awareness and knowledge of glaucoma to encourage their behavior to seek health facilities for eye examinations. The research was carried out in all villages in Taman Sari District. The data was obtained using a questionnaire given to the respondents according to the inclusion criteria. Researchers get a sample of 105 people. The results showed that the level of public knowledge of glaucoma in Taman Sari District, West Jakarta was classified as good. However, people's attitudes and behavior towards glaucoma examinations are still low because of their mindset. The results of the study can be used as a reference to add other variables that may affect knowledge, attitudes and behavior towards glaucoma.